Spatial Patterns and Drivers of Nonperennial Flow Regimes in the Contiguous United States - John C. Hammond; Margaret Zimmer; Margaret Shanafield; Kendra Kaiser; Sarah E. Godsey; Meryl C. Mims; Samuel C. Zipper; Ryan M. Burrows; Stephanie K. Kampf; Walter Dodds; C. Nathan Jones; Corey A. Krabbenhoft; et al. (Geophysical Research Letters)
Abstract Over half of global rivers and streams lack perennial flow, and understanding the distribution and drivers of their flow regimes is critical for understanding their hydrologic, biogeochemical, and ecological functions. We analyzed nonperennial flow regimes using 540 U.S. Geological Survey watersheds across the contiguous United States from 1979 to 2018. Multivariate analyses revealed regional differences in no‐flow fraction, date of first no flow, and duration of the dry‐down period, with further divergence between natural and human‐altered watersheds. Aridity was a primary driver of no‐flow metrics at the continental scale, while unique combinations of climatic, physiographic and anthropogenic drivers emerged at regional scales. Dry‐down duration showed stronger associations with nonclimate drivers compared to no‐flow fraction and timing. Although the sparse distribution of nonperennial gages limits our understanding of such streams, the watersheds examined here suggest the important role of aridity and land cover change in modulating future stream drying.